PENGARUH TIPE BASIS SALEP TERHADAP AKTIVITAS ANTIFUNGI DARI MINYAK ATSIRI KULIT KAYU MANIS CINA (Cinnamomum cassia Nees ex Bl.) PADA PENGHAMBATAN PERTUMBUHAN Candida albicans - C.J. Soegihardjo; Siti Zahliyatul M; Nur Widya Astuti (Universitas Islam Indonesia, 2005)
ABSTRACTCinnamomum cassia Nees ex Bl. is known in the society as Chinese cinnamon. One ofthe uses of Chinese cinnamon is as a fungicide because of its volatile oil contents. The purpose ofthis research was to find out the base type effect of oil base, emulsion base, water soluble basetoward fungicide activity of Chinese cinnamon barks volatile oil on Candida albicans growthinhibition. The fungicide activity test of Chinese cinnamon barks volatile oil in the three base typeusing diffusion methods (agar plate) was done by measuring the diameter of inhibited area towardCandida albicans growth. The inhibited area diameter result was analyzed with one way anova testand continued with Tukey test at 95% confidential level. The obtained result showed that the threebase type was significantly different toward the fungicide activity of chinese cinnamon barks volatileoil. The largest inhibited area (from largest to the lowest) was water soluble base, emulsion base,and oil base.Keywords : minyak cassia, basis salep, Candida albicans